Safety alerts on Rosiglitazone - Subish, P; Isham, MI Mohamed; Mishra, P; Shankar, PR (Journal of Institute of Medicine Nepal, 2010)
The full text of this paper is available from the Journal of Institute of Medicinewebsite Journal of Institute of Medicine, August, 2009; 31:2 32-33